Using YouTube Videos to Teach Students’ Transactional Speaking Skills at Senior High School - Nur Lita; Rahman, Indah Fadhilah (English Language Teaching for EFL Learners Journal, 2024)
This research aims to find out the effectiveness of YouTube videos in teaching transactional speaking skills in the second grade of SMA Negri 12 Luwu. The pre-experimental research with pre-test and post-test was implemented as the design of the research. The population of this research was the second-grade students of SMA Negeri 12 Luwu consisting of 30 students taken using cluster random sampling. The instrument used to collect data was the speaking test. The result of the research presented that using YouTube Videos was effective in improving the students’ Transactional Speaking skills, especially at Class XII IPA B at SMA Negeri 12 Luwu. This implies that the treatment had a significant effect on the students’ transactional speaking skills achievement.